Manajemen Laba: Kontribusi Profitabilitas, Ukuran Perusahaan, dan Leverage Pada Perusahaan Tekstil dan Garmen yang Terdaftar di Bursa Efek Indonesia - Bahtiar Effendi (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
This study aims to determine whether there is influence of profitability, company size and leverage of the company against earnings management. The population in this study is a manufacturing company in the Industrial Sector Textile and Garment in 2015-2017. The sampling technique is done by using non-probability sampling method with saturation sampling technique. Mechanical analysis of data using multiple linear regression methods. The results of data analysis shows that profitability does not significantly influence the earnings management. Profitability shows the company's ability to generate profits for a certain period of time. The market does not respond to profitability as information that can change investor confidence. It cannot effect earnings management practices carried out by the company. The company will not do earnings management by increasing revenue, in order to show shares and retain existing investors. Company size does not significantly effects earnings management. Total assets measure the size of a company as measured by total assets. This does not make managers easy to practice earnings management. Leverage has a significant effect on earnings management. Investors will see the leverage ratio to invest so that it will cause earnings management practices to rise. The high leverage ratio makes the company to practice profit management. Because the company feels threatened to not be able to fulfill its obligations by paying debts on time. Simultaneously profitability, company size and leverage effect companies together on earnings management.